SAE Technical Paper Series 2015
DOI: 10.4271/2015-01-1836
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mixture Formation Process in a Diesel Engine with Post Injection

Abstract: A series of experiments was conducted using a singlecylinder small-bore (85 mm) diesel engine to investigate the smoke-reduction effect of post injection by varying the number of injection nozzle orifices and the injection pressure. The experiments were performed under a constant injection quantity condition and under a fixed NOx emission condition. The results indicated that the smoke emission of six-hole, sevenhole, and eight-hole nozzles decreased for advanced post injection, except that the smoke emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…It was found that the soot reduction response to post-injection timing flattens when the number of nozzle holes is increased. A similar trend was found when a reentrant piston bowl was replaced by a straight-sided variant [13]. Above all, the studies of Horibe and co-workers stress the importance of careful engine hardware selection when employing multipleinjection strategies.…”
Section: Introductionsupporting
confidence: 53%
“…It was found that the soot reduction response to post-injection timing flattens when the number of nozzle holes is increased. A similar trend was found when a reentrant piston bowl was replaced by a straight-sided variant [13]. Above all, the studies of Horibe and co-workers stress the importance of careful engine hardware selection when employing multipleinjection strategies.…”
Section: Introductionsupporting
confidence: 53%